Microstructural Evolution of Cold-Deformed and Isothermally Treated ZA27 Alloys - Desrosin, Wilky (2021)
Pure ZA27 alloys and ZA27 alloys with Cu and Mg additions were cast and deformed by compression. Samples of both alloys were heat treated at 460°C after deformation and the evolution of the microstructure as a function of time measured. The results showed that the average grain size increases with the increase of time for both alloys, with a coarsening rate which is 55% lower for the alloyed ZA27 alloy than the rate of the pure ZA27 alloy. X-ray diffraction analysis indicated that the ZA27 alloys containing Cu and Mg additions present the å phase which is not present in the non-alloyed ZA27 alloy; and that the á and ç phases transform to the â phase during heat treatment. Microhardness measurements showed that the ZA27 alloy with Cu and Mg additions has higher microhardness than the pure ZA27 alloy.